1986
DOI: 10.3109/02713688609015132
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between lacrimal gland, isolated cells (lacrimocytes) and tears: Biochemical and histological studies in the rabbit eye

Abstract: The rabbit defense system has a number of specific features: no lactoferrin and lysozyme are detectable and peroxidase activity is only demonstrated in the cubic epithelial cells of the ducts. Experiments carried out with radioactive amino acid, demonstrate the absence of secreted proteins with molecular weights corresponding to those of albumin and transferrin, indicating that these proteins are not synthesized by the lacrimal gland tissue. Rabbit tear pattern presents a set of acidic proteins secreted by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…A total of 83 third eyelids of adult dogs (8), cats (8), pigs (20), cows (27), sheep (9), goats (3), and horses (8) were investigated in this study. The animals were euthanized for various reasons other than ocular disorders.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 83 third eyelids of adult dogs (8), cats (8), pigs (20), cows (27), sheep (9), goats (3), and horses (8) were investigated in this study. The animals were euthanized for various reasons other than ocular disorders.…”
Section: Methodsmentioning
confidence: 99%
“…Several authors conclude that the immunoglobulins are produced locally, and others suggest that they are mainly supplied from the bloodstream 17 . Sullivan and Allansmith, 18 for example, demonstrated that in the rat the major part of tear IgA comes from local production, as is also the case for humans and rabbits 5,19,20 . Although it is known that tears contain antibodies of the IgA isotype which are produced mainly by plasma cells of the lacrimal gland, very little is known about the antibody source and repertoires in the third eyelid in domestic animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a function of age, lactoferrin concentration tends to decrease (29). In contrast, rabbit tear fluid contains little lactoferrin, and transferrin is detected as an iron-binding protein (30). Therefore, it cannot be concluded from this model that lactoferrin acts on rabbit corneal epithelial cells and inhibits the méthylène blue staining of cornea.…”
Section: Discussionmentioning
confidence: 89%